Efektivitas Kepemimpinan Kepala Selolah Terhadap Kinerja Guru Dalam Penerapan Kurikulum 2013 di SMA Negeri 1 Sanana - sapsuha, irma (JUANGA: Jurnal Agama dan Ilmu Pengetahuan, 2021)
This study aims to find out about the effectiveness of the Principal's leadership on the performance of teachers in the implementation of the 2013 curriculum at Sanana 1 Public High School. Therefore, this research is expected to contribute positively to both the writer and the school in question.Relevant to some of these things, this research focuses on three problem formulations, namely: how is the effectiveness of Principal Leadership in Sanana 1 Public High School? How is the teacher's performance in the implementation of 2013 Curriculum in Sanana 1 Public High School? And how is the Effectiveness of Principal Leadership in implementing the 2013 curriculum in Sanana 1 Public High School. This study uses a type of qualitative research in the form of descriptive data in the form of explanations or interpretations as a whole regarding certain aspects. Methods of collecting data through observation, interviews, and documentation. While to process and analyze data, a descriptive qualitative analysis approach is used, then given meaning to the data collected then a conclusion is drawn. The results of this study indicate that SMA Negeri 1 Sanana is one of the school thas is already quite good in carring out the educational the process.